Analysis of personal psychological motivation and social psychological motivation of Retaliatory Justice under moral public opinion: Chinese cases - Liu, Xi; Zhao, Xiaoying; Wang, Baomin (Frontiers in Psychology, 2022)
From a social psychology perspective, this study explored the personal and social psychological motivation of Retaliatory Justice. This study constructed a four-dimensional model of the psychological motivation of Retaliatory Justice from the two dimensions of “Self vs. Society” and “Identity vs. Resource.” They were Identity-Based Self-Oriented Motivation (Pacifying Outrage), Resource-Based Self-Oriented Motivation (Occupying Resource), Identity-Based Society-Oriented Motivation (Value Confirmation), and Resource-Based Society-Oriented Motivation (Deterrence and Control). In this study, 497 sets of valid data were extracted from 6 universities in Xi'an, Shaanxi Province, China, using 3 sets of situational experiments and the “Questionnaire Star” online survey platform as a vehicle to explore the personal motivations and psychosocial motivations of Retaliatory Justice. The empirical results showed that the situational experiment significantly verified the existence of Pacifying Outrage and Value Confirmation, and partially verified the existence of Deterrence and Control and Occupying Resource. Multiple linear regression analysis showed that only the effect of Pacifying Outrage on Retaliatory Justice showed a main effect, and the interaction between Pacifying Outrage and Deterrence and Control was not significant. Pacifying Outrage significantly affects Retaliatory Justice, while Occupying Resource significantly affects Retaliatory Justice, but the interaction between the two was not significant. Value Confirmation significantly affects Retaliatory Justice. Value Confirmation and Deterrence and Control synergistically affect Retaliatory Justice, but Deterrence and Control had no significant effect on Retaliatory Justice. Taking emotions as clues, this paper discussed the realistic value of the rheological paths of the psychological motivation of Retaliatory Justice, which brought enlightenment to the improvement of social morality, the cultivation of judicial trust, and the construction of psychological service system.